The Pengaruh Rubrik Parametrik dan Transparansi Penalti terhadap Kepercayaan Evaluasi Mahasiswa Non-Desain - Dariyono Dariyono; Muhammad Faizal Rizky; Dion Rimman; Nanada Kurniati (CV. ALIM'SPUBLISHING, 2026)
This mixed-methods study employing a pre-experimental design investigated the effectiveness of implementing a parametric rubric in fostering students’ trust in assessment objectivity within a graphic design course. The evaluation focused on three key aspects: the clarity of assignment instructions, technical constraints related to the use of Figma software, and the transparency of the grading penalty system. Multiple regression analysis revealed that instructional clarity and penalty transparency had a positive and statistically significant effect on students’ trust in grading objectivity, with the penalty component emerging as the most influential factor. In contrast, technical constraints did not demonstrate a statistically significant effect, as they functioned both as a learning support mechanism and as an adaptation burden for students. The implementation of a strict penalty system initially triggered a score shock phenomenon, characterized by a substantial decline in Midterm Examination scores. However, this condition encouraged students to engage in self-evaluation and improve their learning strategies through self-regulated learning. Positive outcomes were reflected in the significant recovery of learning achievement and the more even distribution of student performance by the end of the semester, demonstrating the role of the system as a fair academic safety net for non-design students. Furthermore, 93.1% of students expressed a preference for the objective parametric assessment system over subjective aesthetics-based evaluation. The study concludes that managing examination penalties through a parametric rubric can establish a fair, transparent, and accountable assessment standard in higher education design courses